2009
DOI: 10.1111/j.1096-3642.2008.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Carboniferous origin of the order Mantodea (Insecta: Dictyoptera) gained from forewing morphology

Abstract: Homologies of the forewing venation pattern of the order Mantodea (Insecta: Dictyoptera) consistent with the accepted insect wing venation groundplan are proposed. A comparative morphological analysis was carried out based on a broad taxonomic sample of extant taxa. Besides macromorphological aspects, focus is given to the pattern of the tracheal system as a basis for establishing primary homologies. All extant praying mantids exhibit a composite stem composed of the posterior radius (RP) and the media (M) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 45 publications
2
75
0
Order By: Relevance
“…Béthoux & Wieland (2009) stated that crowngroup-Mantodea are morphologically characterized by the fusion of the RP and M from the wing base in the tegmina (Béthoux & Wieland 2009: 79, 101). Metallyticus and Chaeteessa on the other hand exhibit several plesiomorphic Paraoxypilinae is distributed throughout in Australia and New Guinea with a single species (Exparoxypilus africanus Beier, 1929) having been described from Tanzania.…”
Section: Metallyticus At the Next Dichotomymentioning
confidence: 99%
“…Béthoux & Wieland (2009) stated that crowngroup-Mantodea are morphologically characterized by the fusion of the RP and M from the wing base in the tegmina (Béthoux & Wieland 2009: 79, 101). Metallyticus and Chaeteessa on the other hand exhibit several plesiomorphic Paraoxypilinae is distributed throughout in Australia and New Guinea with a single species (Exparoxypilus africanus Beier, 1929) having been described from Tanzania.…”
Section: Metallyticus At the Next Dichotomymentioning
confidence: 99%
“…cockroaches), asymmetry-which results in variation on a single individual-is common (Bell et al 2007). Venation is less problematic for family level taxonomy, but proves phylogenetically less useful at this level, being frequently convergent (Kristensen 1998), with vein translocation (rapid fusion) common (Béthoux & Wieland 2009). Additionally, different paradigms provide significantly different phylogenetic implications (Béthoux 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Appendage details could provide new characters for phylogeny and greatly improve our knowledge of the palaeoecology of Carboniferous insects, but relatively few have hitherto been described (e.g. Béthoux 2009). Garwood et al (2009) demonstrated that a microtomography (mCT)-based 'virtual palaeontology' approach can extract appendage data from siderite nodule fossils; we apply this method here to a blattopteran fossil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1994 there have been major changes to insect taxonomy (e.g. [25]), the estimated ages of deposits (e.g. [26]), about 400 additional insect families are known from the fossil record [27] and 21% of the families in Labandeira [24] have since been synonymized.…”
Section: Introductionmentioning
confidence: 99%